2011
DOI: 10.1007/s11357-011-9207-7
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Ang II involvement in activation of NF-κB through phosphorylation of p65 during aging

Abstract: Angiotensin II (Ang II), a major effector of the renin-angiotensin system, is now recognized as a pro-inflammatory mediator. This Ang II signaling, which causes transcription of pro-inflammatory genes, is regulated through nuclear factor-κB (NF-κB). At present, the molecular mechanisms underlying the effect of aging on Ang II signaling and NF-κB activation are not fully understood. The purpose of this study was to document altered molecular events involved in agerelated changes in Ang II signaling and NF-κB ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 54 publications
3
26
0
1
Order By: Relevance
“…Interestingly, also the chymase, another angiotensin-convertase, was found in the wall of aged aorta [69]. Recently, two additional groups [70,71] evidenced that Ang II signaling cascades promote aorta remodeling by Fig. 4.…”
Section: Structural and Functional Features Of The Aorta In Physiologmentioning
confidence: 91%
See 2 more Smart Citations
“…Interestingly, also the chymase, another angiotensin-convertase, was found in the wall of aged aorta [69]. Recently, two additional groups [70,71] evidenced that Ang II signaling cascades promote aorta remodeling by Fig. 4.…”
Section: Structural and Functional Features Of The Aorta In Physiologmentioning
confidence: 91%
“…This evidence is the result of findings from the Lakatta s' group, using rat models, [62,63], and Šabovic's group [64], who propose administering combination of low-dose fluvastatin and valsartan, as anti-aging drugs. On the other hand, the expression and activity of Ang II, the angiotensin converting enzyme (ACE), the Ang II receptor AT1 receptor within the aorta wall, in particular, in the thickened intima in several species, including humans, are risen as the age progress [62][63][64][65][66][67][68][69][70][71]. Interestingly, also the chymase, another angiotensin-convertase, was found in the wall of aged aorta [69].…”
Section: Structural and Functional Features Of The Aorta In Physiologmentioning
confidence: 99%
See 1 more Smart Citation
“…Ang II activates NF-κB via AT1R in vascular cells and mononuclear cells, both in vivo and in vitro [59,60]. The increase Ang II activates NF-κB by phosphorylating IκBα and p65 [61], which induces enhanced matrix metalloproteinase 9 (MMP-9) expression [62]. The AT1R mediates most of the actions of Ang II, but experimental data suggest that AT2R is also involved in Ang II-mediated NF-κB activation in inflammatory cell recruitment [63].…”
Section: Role Of Ras In Atherosclerosis Developmentmentioning
confidence: 99%
“…Experimental data suggest that age-related NF-κB activation is affected by AGE-induced NADPH oxidase activation [18]. Recent work from Kim et al [19] has shown that angiotensin II, a major effector of the rennin-angiotensin system, influences the phosphorylation of p65-mediated NF-κB activation during aging. Increased phosphorylation of p65 at Ser 536 was mediated by the enhanced phosphorylation of IKK, while phosphorylation site Ser 276 of p65 was mediated by upregulated MSK-1.…”
Section: Age-related Redox Imbalance and Redox Signaling Pathwaymentioning
confidence: 99%